EFFECTS OF POULTRY BUILDING DESIGN ON INDOOR AIR QUALITY IN HUMID CLIMATES - H. E. Polat (Journal of Animal and Plant Sciences, 2015)
In this study, six poultry buildings, consisting of four layer hen houses and two broiler houses located in Manisa Province in Turkey, were examined to find out the effects of planning systems on indoor environmental conditions where the age of litter for broiler ranged from 4-18 weeks and the age of commercial layer hens ranged from 22-43 weeks. Air quality parameters, as concentrations of ammonia, carbon dioxide and methane were measured by using multi-gas monitor. Other parameters, as temperature/relative humidity and particulate matter were measured by using respectively, psychrometric sensors and multi-function meter. These measurements were obtained as four replicates for each building in winter, early spring, and summer. The measured data were evaluated via repeated measures analysis of variance (rANOVA). According to the research results, measured indoor temperature values tend to rise in Californian cage type buildings in all seasons (max. 27.65 °C in winter and max. 41.85 °C in summer). The highest relative humidity values were measured in deep litter type buildings (max. 76.27 % in winter and max. 80.44 % in summer). Particulate matter levels had high values in Californian cage type buildings in summer (Avg. 1.09 mg/m3) and in deep litter type buildings in winter (Avg. 3.16 mg/m3). Concentrations of NH3 and CH4 had high levels in Californian cage type (34.68 ppm NH3 and 15.14 ppm CH4 max. values) and deep litter type (49.54 ppm NH3 and 19.32 ppm CH4 max. values) buildings in winter. NH3 and CH4 have a tendency to rise in all types of buildings in summer. CO2 had the highest levels in Californian cage type (max. 1805.57 ppm) and deep litter type (max. 8906.33 ppm) buildings in all seasons. Concentrations of CO2 had lower levels in summer than in winter in all types of poultry buildings. Statistical analysis showed that the design of poultry buildings determined indoor environmental conditions. Also, hot and humid local climate has the effects on indoor air quality.
Keywords: ammonia; broiler; carbon dioxide; laying hen; methane; particulate matter